ANALISIS NILAI MORAL KUMPULAN CERPEN “MALAM TERAKHIR” KARYA LEILA S. CHUDORI - Hudan Rahmatullah; Jagat Warisandani; Saepul Romdon; Raden Mekar Ismayani (IKIP Siliwangi, 2018)
The decline of moral values that occur in the community is increasingly of concern, especially among students/learners. We know that students are now increasingly becoming so immoral, a lot of students who are immoral even dare to kill their teacher. The education of moral values must be inserted in any language and literature learning, one of them by reading a short story which has a lot of good moral values. This study aims to analyze the forms of moral values that contained in the short story entitled Malam Terakhir. This analysis uses a structural approach to read and identify the intrinsic elements of the short story. Data collection in this research by reading and marking the text or sentence that is included moral values. So moral values that contained in the short story are easily identified. Based on the results of the analysis of the short story collection “Malam Terakhir